Kazimir Malevich’s Negative Theology and Mystical Suprematism - Irina Sakhno (Religions, 2021)
This article examines Kazimir Malevich’s Suprematist art in the context of negative (apophatic) theology, as a crucial tool in analyzing both the artist’s theoretical conclusions and his new visual optics. Our analysis rests on the point that the artist intuitively moved towards recognizing the ineffability of the multidimensional universe and perceiving God as the Spiritual Absolute. In his attempt to see the invisible in the formulas of Emptiness and Nothingness, Malevich turned to the primary forms of geometric abstraction—the square, circle and cross—which he endows with symbolic concepts and meanings. Malevich treats his Suprematism as a method of perceiving the ineffability of the Absolute. With the Black Square seen as a face of God, the patterns of negative theology rise to become the philosophical formula of primary importance. Malevich’s Mystical Suprematism series (1920–1922) confirms the presence of complex metaphysical reflection and apophatic thought in his art. Not only does the series contain icon paraphrases and the Christian symbolism of the cross and mandorla, but it also advances the formulas of the apophatic faith of the modern times, since Suprematism presents primary forms as the universals of “the face of the future” and the energy of the non-objective art.